Eosinophils preserve bone homeostasis by inhibiting excessive osteoclast formation and activity via eosinophil peroxidase. - Andreev, Darja; Kachler, Katerina; Liu, Mengdan; Chen, Zhu; Krishnacoumar, Brenda; Ringer, Mark; Frey, Silke; Krönke, Gerhard; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2024)
Eosinophils are involved in tissue homeostasis. Herein, we unveiled eosinophils as important regulators of bone homeostasis. Eosinophils are localized in proximity to bone-resorbing osteoclasts in the bone marrow. The absence of eosinophils in ΔdblGATA mice results in lower bone mass under steady-state conditions and amplified bone loss upon sex hormone deprivation and inflammatory arthritis. Conversely, increased numbers of eosinophils in IL-5 transgenic mice enhance bone mass under steady-state conditions and protect from hormone- and inflammation- mediated bone loss. Eosinophils strongly inhibit the differentiation and demineralization activity of osteoclasts and lead to profound changes in the transcriptional profile of osteoclasts. This osteoclast-suppressive effect of eosinophils is based on the release of eosinophil peroxidase causing impaired reactive oxygen species and mitogen-activated protein kinase induction in osteoclast precursors. In humans, the number and the activity of eosinophils correlates with bone mass in healthy participants and rheumatoid arthritis patients. Taken together, experimental and human data indicate a regulatory function of eosinophils on bone.
EVALuna2:554518

INDUCTION OF TH2 CELLS AND EOSINOPHIL BY INFECTION WITH NIPPOSTRONGYLUS BRASILIENSIS PROTECTS AGAINST RHEUMATOID ARTHRITIS - Chen, Zhu; Oeser, Katharina; Baum, Wolfgang; Vöhringer, David; Schett, Georg; Bozec, Aline (2014)
EVALuna2:13204

T Cell Costimulation Molecules CD80/86 Inhibit Osteoclast Differentiation by Inducing the IDO/Tryptophan Pathway - Bozec, Aline; Zaiss, Mario; Kagwiria, Rosebeth; Voll, Reinhard; Rauh, Manfred; Chen, Zhu; Müller-Schmucker, Sandra; Kroczek, Richard A.; Heinzerling, Lucie; Moser, Muriel; Mellor, Andrew L.; David, Jean-Pierre; et al. (Science Translational Medicine, 2014)
Bone resorption is seminal for the physiological remodeling of bone during life. However, this process needs to be strictly controlled; excessive bone resorption results in pathologic bone loss, osteoporosis, and fracture. We describe a control mechanism of bone resorption by the adaptive immune system. CD80/86, a pair of molecules expressed by antigen-presenting cells and involved in T cell costimulation, act as negative regulator for the generation of bone-resorbing osteoclasts. CD80/86-deficient mice were osteopenic because of increased osteoclast differentiation. CD80/86-deficient osteoclasts escaped physiological inhibition by CTLA-4 or regulatory T cells. Mechanistically, engagement of CD80/86 by CTLA-4 induced activation of the enzyme indoleamine 2,3-dioxygenase (IDO) in osteoclast precursors, which degraded tryptophan and promoted apoptosis. Concordantly, IDO-deficient mice also showed an osteopenic bone phenotype with higher numbers of osteoclast precursors and osteoclasts. Also, IDO-deficient mononuclear cells escaped the anti-osteoclastogenic effect of CTLA-4. This molecular mechanism was also present in humans because targeting CD80/86 by abatacept, a CTLA-4-immunoglobulin fusion protein, reduced, whereas blockade of CTLA-4 by ipilimumab antibody enhanced, the frequency of peripheral osteoclast precursors and osteoclastogenesis. In summary, these data show an important role of the adaptive immune system, in particular T cell CD80/86 costimulation molecules, in the physiological regulation of bone resorption and preservation of bone mass, as well as affect the understanding of the function of current and future drugs fostering or blocking the effects of CTLA-4 in humans.
EVALuna2:12912

Th2 and eosinophil responses ameliorate arthritis and inflammatory bone loss - Andreev, Darja; Chen, Zhu; Oeser, Katharina; Krljanac, B.; Hueber, Axel; Kleyer, Arnd; Weigmann, Benno; Vöhringer, David; Schett, Georg; Bozec, Aline (2017)
EVALuna2:33419

Th2 and eosinophil responses suppress inflammatory arthritis - Chen, Zhu; Andreev, Darja; Oeser, Katharina; Krljanac, Branislav; Hueber, Axel; Kleyer, Arnd; Vöhringer, David; Schett, Georg; Bozec, Aline (Nature Communications, 2016)
Th2-eosinophil immune responses are well known for mediating host defence against helminths. Herein we describe a function of Th2-eosinophil responses in counteracting the development of arthritis. In two independent models of arthritis, Nippostrongylus brasiliensis infection leads to Th2 and eosinophil accumulation in the joints associated with robust inhibition of arthritis and protection from bone loss. Mechanistically, this protective effect is dependent on IL-4/IL-13-induced STAT6 pathway. Furthermore, we show that eosinophils play a central role in the modulation of arthritis probably through the increase of anti-inflammatory macrophages into arthritic joints. The presence of these pathways in human disease is confirmed by detection of GATA3-positive cells and eosinophils in the joints of rheumatoid arthritis patients. Taken together, these results demonstrate that eosinophils and helminth-induced activation of the Th2 pathway axis effectively mitigate the course of inflammatory arthritis.
EVALuna2:13286